Mitoxantrone treatment-induced cardiotoxicity in patients with multiple sclerosis - Martins, Diana Mafalda Miranda (2015)
Multiple Sclerosis (MS) is a chronic, autoimmune, neurodegenerative and demyelinating disease of the central nervous system, which affects the quality of life of patients and their families. This disease is characterized by relapses or exacerbations, which are clinical consequences of increased inflammatory activity in the CNS. Few treatment options for patients with secondary progressive multiple sclerosis (SPMS) is available. Mitoxantrone (type II topoisomerase inhibitor) could be used to treat MS, most notably the subset known as SPMS. Mitoxantrone will not cure MS, but could be effective in slowing the progression of SPMS and extending the time between relapses in relapsing-remitting MS and progressive relapsing MS.